The burden of hypertension in future doctors: a phase-wise cross-sectional study - Jilani, Mohammed Saquib Mohammed; Asifali, Shaikh Abid; Khan, Mohammed Aasem Khan Aslam; Munaf, Momin Sohel; Solanke, Sachin N.; Chhabda, Dhiraj Shantilal; Javeriya, Sana (International Journal of Research in Medical Sciences, 2025)
Background: Hypertension is a growing concern in young adults, yet most studies focus on the elderly. Investigating its prevalence and risk factors in younger populations can enable timely interventions to prevent long-term complications. Medical students, facing academic stress and lifestyle changes, are particularly vulnerable. This study assessed hypertension prevalence and blood pressure variations across four academic phases. Methods: A cross-sectional analytic study was conducted among 499 medical students aged 18–27 from four academic phases. Participants were selected through multi-stage sampling, and demographic, anthropometric, and clinical data were collected. Blood pressure was measured using an Omron HBP-1320 device, validated per ANSI/AAMI/ISO and ESH IP2 protocols, with classification based on AHA guidelines. Statistical analyses included ANOVA, chi-squared tests, and Spearman’s correlation. Results: Median age increased from 20 years in phase 1 to 23 in phase 4. Mean BMI rose from 22.07±4.01 kg/m² to 23.51±4.67 kg/m². Systolic blood pressure increased across phases but was not statistically significant (p=0.223). Diastolic pressure rose significantly (p=0.011), with hypertension prevalence escalating from 19.5% to 41.2%. Males exhibited higher SBP, DBP, and pulse pressure (p<0.001). Positive correlations were observed between age, BMI, and blood pressure. Conclusion: The study highlights a rising trend in stage 1 hypertension and diastolic pressure with academic progression, likely due to stress and lifestyle changes. Males had higher blood pressure levels. Early interventions targeting modifiable risk factors are essential to prevent long-term complications.